Effect of Hormone Types and Concentrations on In Vitro Multiplication and Growth of Pineapple (Ananas Comosus (L.) Merr.) Cv Moris on Liquid MS Medium - Hamad, Abdelhamid M. (Al-Mukhtar Journal of Sciences, 2017)
The effect of two cytokinins, 6-benzyleaminopurine (BAP) and kinetin (KN) and two auxins, naphthalene acetic acid (NAA) and indole acetic acid (IAA) each applied at 10 concentrations with an increment of 0.5 mg/l in the in vitro shoot formation of Moris pineapple was evaluated in static liquid MS medium. The highest shoot formation (9 shoots per explant) was obtained in medium enriched with NAA but at high concentration (4.5 mg/l). The second best was 8 shoots per explant obtained in medium enriched with BAP at 2.0 mg/l. Out of 10 concentrations, NAA was better than BAP at the highest 5 and less at lowest 5 concentrations and at all concentrations both hormones resulted in production of more shoots per explant than hormone free medium. Except at two concentrations, NAA and BAP were better than KN. Either one of these three hormones, BAP, NAA, KN could be claimed, depending on the tested range of concentrations, better than the others for in vitro shoot formation of Moris pineapple. All of the IAA concentrations, on the other hand, failed to produce more shoots than hormone free medium. But, the longest shoot (56 mm) obtained in medium enriched with IAA at 2.5 mg/l and the shortest shoots (6 mm) on medium enriched with KN at 4.0 mg/l. Seven of the IAA concentrations resulted in shoots longer than hormone free medium (27 mm) while the shoots length on the BAP, NAA and KN contained media was two times shorter than hormone free medium. BAP at 2.0 mg/l was the best treatment for multiplication and IAA at 2.5 mg/l was the best for elongation of Moris pineapple.